2019
DOI: 10.1111/ejn.14608
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for spontaneous cross‐frequency phase–phase coupling in the human hippocampus

Abstract: Cross‐frequency phase–phase coupling (PPC) has been suggested to play a role in cognitive processing and, in particular, in memory consolidation during sleep. Controversial results have been reported regarding the existence of spontaneous phase–phase coupling in the hippocampus. Here, we investigated this phenomenon in intracranial EEG recordings from the human hippocampus acquired during waking state and different sleep stages. We estimated the strength of interactions between different pairs of frequency ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“… 68 , 69 , 70 Yet, such investigations on underlying mechanisms are challenging: For instance, in rodents with well pronounced hippocampal activity NREM sleep depths are less distinct than in humans; on the other hand, humans revealed an unclear degree of systematic hippocampal coupling to cortical oscillations. 60 , 71 , 72 Regarding the thalamic contributions, despite successful findings 73 far-field electrophysiological thalamic measurements are technically hampered by the non-laminar structure and electrical closed-field properties. 74 …”
Section: Discussionmentioning
confidence: 99%
“… 68 , 69 , 70 Yet, such investigations on underlying mechanisms are challenging: For instance, in rodents with well pronounced hippocampal activity NREM sleep depths are less distinct than in humans; on the other hand, humans revealed an unclear degree of systematic hippocampal coupling to cortical oscillations. 60 , 71 , 72 Regarding the thalamic contributions, despite successful findings 73 far-field electrophysiological thalamic measurements are technically hampered by the non-laminar structure and electrical closed-field properties. 74 …”
Section: Discussionmentioning
confidence: 99%
“…For properties of interactions, constrained realizations of the multivariate time series can be generated by randomizing the aspect of a recorded dynamics on which the estimator for the property of an interaction is based ( Schreiber, 1998 ; Schreiber and Schmitz, 2000 ; Andrzejak et al, 2003a ; Paluš, 2007 ; Rings et al, 2020 ). However, the associated surrogate techniques are exclusively designed for the strength of an interaction as the formulation of null hypotheses for the direction of an interaction (linkable to properties of time series for an appropriate null model) continues to be an unsolved problem.…”
Section: Techniques To Assess and Characterize A Time-evolving Brain ...mentioning
confidence: 99%
“…Alpha (8-12 Hz) rhythms in the human brain were first observed in 1928 [7]. Other characteristic brain activities have also been successively investigated, including the delta (0.5-4 Hz), theta (4-8 Hz), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (above 30 Hz) frequency bands [8][9][10]. Moreover, it was found that the neural oscillations in different frequency bands interact mutually, which is called cross-frequency coupling (CFC) in the literature [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been proven that CFC is a pathological pattern in various conditions correlating with symptom severity [21][22][23]. Most previous studies focused on the following three types of CFCs: PAC [24][25][26], phase-phase coupling (PPC) [27][28][29] and amplitude-amplitude coupling (AAC) [30,31]. Here, we intended to make contributions to measuring the PAC because of its significant role in neural information processing [16,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%